Research on backup and remapping of network slice based on security classification - Zhiyong SUN; Xinsheng JI; Wei YOU; Quan YUAN (网络与信息安全学报)
In the future virtual environment of 5G core network,the general X86 servers make the attackers exploit vulnerabilities more easily,the substrate network is infected with and spreads the virus more easily,and the problem of single physical node failed will affect the service performance of the network slice seriously.Based on the existing node backup and remapping solutions,considering the impact of security constraints among nodes on network security performance,a security parameter evaluation model of virtual nodes and physical nodes were proposed in the network slicing,and the security constraint relationship was established between the virtual nodes and the physical nodes.Then backup virtual nodes were selected based on the security parameters evaluation model,and backup mapping methods were designed.Finally,the node remapping mechanism was designed with satisfying the requirement of network delay.Experiments show that the proposed method can significantly improve network intrusion tolerance with satisfying the requirements of network slicing service performance.